2018
DOI: 10.3390/ijerph15020241
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mental Disorders and Addictions among Homeless People in the Greater Paris Area, France

Abstract: The Samenta study was conducted in 2009 in the Greater Paris area to estimate the prevalence of psychiatric disorders in homeless people. A cross-sectional survey was performed with a three-stage random sample of homeless people (n = 859), including users of day services, emergency shelters, hot meal distribution, long-term rehabilitation centres, and social hotels. Information was collected by a lay interviewer, using the Mini International Neuropsychiatric Interview, and completed by a psychologist through a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 46 publications
1
48
2
1
Order By: Relevance
“…Additionally, the literature tends to treat the settlement, health, and homelessness of foreign-born people as separate agendas [ 4 , 17 ]. Despite growing evidence that foreign-born people make up an increasing proportion of the homeless population, very few studies analyze the issue in terms of health and mortality [ 18 , 19 ]. These gaps must be filled in order to design successful interventions and achieve better health and financial outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the literature tends to treat the settlement, health, and homelessness of foreign-born people as separate agendas [ 4 , 17 ]. Despite growing evidence that foreign-born people make up an increasing proportion of the homeless population, very few studies analyze the issue in terms of health and mortality [ 18 , 19 ]. These gaps must be filled in order to design successful interventions and achieve better health and financial outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A second study, “La Santé Mentale et les addictions chez les personnes sans logement personnel d’Ile-de-France”—SAMENTA (Prevalence of Mental Disorders and Addictions among Homeless People)—was conducted among homeless people and found three times more depressive episodes and six times more post-traumatic stress disorder (PTSD) among migrants in comparison with natives [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Participants reported an inextricable connection between their health and homelessness. Likewise, several studies reported an association between homelessness and higher rates of infectious disease, injury, substance use, psychiatric illness, and accident and emergency admissions [56,57,58,59,60].…”
Section: Discussionmentioning
confidence: 99%